2002
DOI: 10.1182/blood.v99.4.1282
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increase in lymph node dendritic cell number during infection by the mouse mammary tumor virus occurs by a CD62L-dependent blood-borne DC recruitment

Abstract: IntroductionDendritic cells (DCs) play a central role in the immune system due to their main function as initiators and regulators of antigenspecific antiviral T-cell responses and in the pathogenesis of a variety of viruses, such as human immunodeficiency virus (HIV), cytomegalovirus, measles virus, herpes virus, influenza virus, and respiratory syncytial virus. 1 However, little is known about the subpopulations of DCs involved in antiviral responses, the kinetics of the variations of DC subpopulations, and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…Thus, it is likely that the expression of CCR7 accounts for the augmented migration of 3h-DCs and reduced migration of 24h-DCs. Although it was reported that CD62L, which recognizes high endothelial venules, plays an important role in the migration of DCs to secondary lymphoid organs (46), no expression of CD62L was detected on DCs stimulated for 0, 3, or 24 h with immobilized anti-CD40 Ab (data not shown). Subcutaneous inoculation of 3h-DCs induced a marked increase in the total number of cells and the percentage of Ag-primed T cells, which were depicted as T cells with down-regulated CD62L expression, in the draining LNs (Figs.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it is likely that the expression of CCR7 accounts for the augmented migration of 3h-DCs and reduced migration of 24h-DCs. Although it was reported that CD62L, which recognizes high endothelial venules, plays an important role in the migration of DCs to secondary lymphoid organs (46), no expression of CD62L was detected on DCs stimulated for 0, 3, or 24 h with immobilized anti-CD40 Ab (data not shown). Subcutaneous inoculation of 3h-DCs induced a marked increase in the total number of cells and the percentage of Ag-primed T cells, which were depicted as T cells with down-regulated CD62L expression, in the draining LNs (Figs.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, MMTV has been shown to interact with DCs. Both experimental subcutaneous inoculation with MMTV and milk-borne infection produce dramatic increases in the numbers of DCs in the draining lymph nodes and Peyer's patches, respectively (8,24). In addition, DCs can be infected by MMTV and can present Sag to T cells, suggesting their involvement in the early phase of infection (5,24,38).…”
mentioning
confidence: 99%
“…Both experimental subcutaneous inoculation with MMTV and milk-borne infection produce dramatic increases in the numbers of DCs in the draining lymph nodes and Peyer's patches, respectively (8,24). In addition, DCs can be infected by MMTV and can present Sag to T cells, suggesting their involvement in the early phase of infection (5,24,38). Finally, it has been demonstrated that MMTV can induce DC maturation and up-regulation of surface expression of the virus entry receptor transferrin receptor 1 (TfR1) via interaction with Toll-like receptor 4 (TLR4) (8).…”
mentioning
confidence: 99%
“…Infection leads to the recruitment of pDCs and CD8 + DCs into the draining lymph node from the blood (32)(33)(34)43). The influx of pDC is dependent on b 1 -and b 2 -integrins, CXCL9 and E-selectin Data are mean number of cells per lymph node 6 SE based on 10-15 mice/group from two to three independent experiments.…”
Section: Discussionmentioning
confidence: 99%